EGFR tyrosine kinase inhibitors versus chemotherapy in EGFR wild-type pre-treated advanced nonsmall cell lung cancer in daily practice. Issue 2 (10th August 2017) - Tomasini, Pascale; Brosseau, Solenn; Mazières, Julien; Merlio, Jean-Philippe; Beau-Faller, Michèle; Mosser, Jean; Wislez, Marie; Ouafik, L'Houcine; Besse, Benjamin; Rouquette, Isabelle; Debieuvre, Didier; Escande, Fabienne; et al.
Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) are approved for second-line treatment of EGFR wild-type ( EGFR -wt) nonsmall cell lung cancer (NSCLC). However, results from randomised trials performed to compare EGFR-TKIs with chemotherapy in this population did not show any survival benefit. In the era of immunotherapy, many drugs are approved for second-line treatment of EGFR- wt NSCLC and there is a need to reassess the role of EGFR-TKIs in this setting. The Biomarkers France study is a large nationwide cohort of NSCLC patients tested for EGFR mutations. We used this database to collect clinical, biological, treatment and outcome data on EGFR- wt patients who received second-line treatment with either EGFR-TKIs or chemotherapy. Among 1278 patients, 868 received chemotherapy and 410 received an EGFR-TKI. Median overall survival and progression-free survival were longer with chemotherapy than with an EGFR-TKI. Overall survival was 8.38 versus 4.99 months, respectively (hazard ratio 0.70, 95% CI 0.59–0.83; p<0.0001) and progression-free survival was 4.30 versus 2.83 months, respectively (hazard ratio 0.66, 95% CI 0.57–0.77; p<0.0001). This study is helpful to guide a multiline treatment strategy for EGFR- wt NSCLC patients. Immunotherapy is approved for second-line treatment. For third-line treatment, chemotherapy results in longer overall survival and progression-free survival, and should be preferred to EGFR-TKIs. Biomarkers France study: second-line chemotherapy gave longer PFS and OS than TKI in NSCLC EGFR -wt patients http://ow.ly/rEXk30b3tak